دور استخدام مواقع التواصل الاجتماعي في تفعيل أنشطة العلاقات العامة (دراسة ميدانية في جامعة تشرين) - قاسم, سامر; محمد, رامي; محلا, براءة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This study aims to determine the relationship between the use of The Social Media and the activation of public relations activities at Tishreen University. The researcher relied on both the methodological approach as a general approach to research, and the descriptive approach and distributed a questionnaire to (303) employees of the central administration at Tishreen University, (274) questionnaires were retrieved, valid for the use of (264) questionnaires. A field study was carried out for the purpose of explaining this relationship. The researcher used the Pearson correlation coefficient. The study concluded that there is a significant positive relationship between the use of the Social Media and the activation of public relations activities; The study also reached a set of recommendations and proposals that would positively contribute to improving the role of the university's page on The Social Media in activating public relations activities. هدفت هذه الدّراسة إلى تحــديــد العلاقـة بين استخدام مواقع التواصل الاجتماعي وتفعيل أنشطة العلاقات العامة في جامعة تشرين، وقد اعتمدت الباحثة على كل من المقاربة الاستنباطيَّة كمنهج عام للبحث، والمنهج الوصفي، وقامت بتوزيع استبانة على (303) من العاملين في الإدارة المركزيّة في جامعة تشرين، تمَّ استرداد (274) استبانة، كان صالحاً منها للاستخدام (264) استبانة، ومن ثمَّ أجريت دراسة ميدانيّة بغرض بيان هذه العلاقة، حيث قامت الباحثة باستخدام معامل ارتباط بيرسون (Pearson). وقد خلصت الدّراسة إلى وجود علاقة طرديّة معنويّة بين استخدام مواقع التواصل الاجتماعي وتفعيل أنشطة العلاقات العامة؛ وبالتَّالي وجود دور لاستخدام مواقع التواصل الاجتماعي في تفعيل أنشطة العلاقات العامة في جامعة تشرين؛ كما توصّلت هذه الدّراسة إلى مجموعة من التّوصيات والمقترحات، والَّتي من شأنها أن تسهم بشكلٍ إيجابي بتحسين دور صفحة الجامعة على مواقع التواصل الاجتماعي في تفعيل أنشطة العلاقات العامة.